Penerapan Business Model Canvas (BMC) Pada Bisnis Pengolahan Kakao Kelompok Wanita Tani di Desa Sungai Langka, Kecamatan Gedong Tataan, Kabupaten Pesawaran, Kabupaten Pesawaran - Handayani, Sri; Kusmaria, Kusmaria (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Cocoa (Theobroma cacao L) is one of Indonesia's leading export commodities which can be processed into a variety of snacks and also a mixture of food products. The Women Farmer Group (KWT) of Sungai Langka Village, Gedong Tataan District, Pesawaran Regency is a cocoa processing business group that processes cocoa products from most of the cocoa farmers in the area. The purpose of this study was to identify the application of the cocoa processing business model to women farmer groups in Sungai Langka Village, Gedong Tataan District, Pesawaran Regency. This research was conducted from June to November 2022. The data analysis method used is descriptive analysis through the identification of business models using the Business Model Canvas (BMC). Data collection was carried out using a survey method (interviews) on all 22 KWT members. The results of the study show that there is an advantage in the value element in processed cocoa products in the form of healthy food due to minimal use of chemicals and preservatives so it is good for health. In addition, the KWT Sungai Langka cocoa processing business also has the advantage of supporting local wisdom and economic empowerment of cocoa farmers.